2005
DOI: 10.4049/jimmunol.175.11.7457
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Encodes an MHC Class I-Like Molecule (UL142) That Functions to Inhibit NK Cell Lysis

Abstract: Clinical and low passage strains of human CMV (HCMV) encode an additional MHC class I-related molecule UL142, in addition to the previously described UL18. The UL142 open reading frame is encoded within the ULb′ region which is missing from a number of common high passage laboratory strains. Cells expressing UL142 following transfection, and fibroblasts infected with a recombinant adenovirus-expressing UL142, were used to screen both polyclonal NK cells and NK cell clones, in a completely autologous system. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 44 publications
(46 reference statements)
1
108
0
1
Order By: Relevance
“…Anti-hamster CD63 hybridoma was provided by Dr. M. Marsh (clone eh1C9b, generated by S. Schmid). NK primary cell lines were generated from healthy donor peripheral blood mononuclear cells as described (30).…”
Section: Methodsmentioning
confidence: 99%
“…Anti-hamster CD63 hybridoma was provided by Dr. M. Marsh (clone eh1C9b, generated by S. Schmid). NK primary cell lines were generated from healthy donor peripheral blood mononuclear cells as described (30).…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, the UL/b' region has been demonstrated to be important for the dissemination, latency and virulence of HCMV in human hosts (9)(10)(11)(12). The UL142 ORF, located within the UL/b' region, is 921 bp in length and is predicted to encode a protein, presumably an important component in the inhibition of natural killer (NK) cell killing and the innate defense against HCMV (13).…”
Section: Introductionmentioning
confidence: 99%
“…UL142 is a member of the UL18 gene family (36) and is predicted to have structural similarities to MHC class I, with a1 and a2 domains but no a3 domain. In addition, we previously showed that UL142 localizes to the ER and cis-Golgi (37,38) and that transduction of UL142 is sufficient to protect cells from NK cell-mediated lysis, whereas reducing UL142 translation with RNA interference during HCMV infection increases NK cellmediated cytotoxicity (37). UL142 can also downregulate the products of full-length alleles of MICA by intracellular retention in the Golgi complex (33,38).…”
mentioning
confidence: 99%